(untitled) (At-Tibyan, 2023)
Studies that discuss women’s issues are numerous and very interesting because women are the most important part of society, especially the discussion of career women. Therefore, this research aims to discuss the concept of career women in the maqashid shari’ah interpretation method which can help in the interpretation and application of Islamic law in various contexts and times, especially about career women. This research uses a qualitative method through a literature approach that studies various references and the results of previous similar studies. The results of this study indicate that everyone is free to choose a profession that suits their choice and there are no restrictions, including to women. So women are allowed to have a career as long as it brings benefits and benefits to them, their families, and society.